Computing Transpiration and Soil Evaporation from Periodic Soil Moisture Measurements and other Physical Data - Banerjee, A. K. (Indian Forester, 1973)
Transpiration and evaporation from a planted forest of Alstonia scholaris of 20 years of old at Arabari Range of East Midnapore Division in Midnapore District of West Bengal has been computed in an indirect manner from moisture measurements taken at periodic intervals of 1970-71 and from the evaporation data collected through U.S. pan evaporimeters installed in the plantation site and in an adjoining bare land. It was found that during the study period the total rainfall was 162.28 cm while the loss due to interception, evaporation and transpiration during the period was 34.50 cm, 56.80 cm and 73.62 cm respectively. It has been discussed that very close spacing of plants to reduce evaporation and make more water available to them to boost up their growth is a possibility in Semi-arid regions.